2017
DOI: 10.1089/jir.2016.0088
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Risk Association Between Interleukin-17A and F Gene Polymorphisms and Inflammatory Diseases

Abstract: This meta-analysis examined the relationship between IL-17A (rs2275913) and IL17F (rs763780 T/C) gene polymorphisms and the risk of inflammatory diseases, including periodontitis, rheumatoid arthritis (RA), and inflammatory bowel disease. PubMed, MEDLINE, EMBASE, Web of Science, and Elsevier Science Direct were searched, and odds ratios (ORs) with 95% confidence interval (CI) were calculated to estimate the strength of the association. A total of 25 studies comprising 7,474 cases and 10,628 controls were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 35 publications
0
29
1
2
Order By: Relevance
“…On the other hand, the Th17 profile has been studied widely in autoimmune diseases and has been described as a risk factor. For example, there are studies of SNPs in IL17A associated with rheumatoid arthritis and systemic lupus erythematosus [8][9][10][11] , but there are not enough studies in COPD, despite the pathophysiological role of IL17 and Th17 cells. Since 2003, Agustí and coworkers 12 hypothesized that one of the possible pathogenic mechanisms in COPD is the existence of self-perpetuating inflammation, similar to other autoimmune diseases.…”
mentioning
confidence: 99%
“…On the other hand, the Th17 profile has been studied widely in autoimmune diseases and has been described as a risk factor. For example, there are studies of SNPs in IL17A associated with rheumatoid arthritis and systemic lupus erythematosus [8][9][10][11] , but there are not enough studies in COPD, despite the pathophysiological role of IL17 and Th17 cells. Since 2003, Agustí and coworkers 12 hypothesized that one of the possible pathogenic mechanisms in COPD is the existence of self-perpetuating inflammation, similar to other autoimmune diseases.…”
mentioning
confidence: 99%
“…Another meta-analysis including four studies also observed a positive association between IL-17F 7488A/G and RA susceptibility. 30 However, caution should be taken for the conclusion of this meta-analysis since a study on osteoarthritis was included in the RA group. 31 There were several strengths of our work.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, IL-17 was considered as one of pro-in ammatory cytokines, and IL-17 could initiate the release of pro-in ammation cytokines and chemokines, , matrix metalloproteinases, and antimicrobial peptides from myeloid cells, mesenchymal cells and even epithelial cells [11]. Recently, IL-17 has emerged as an important driver of pathogenic in ammation, and is considered a key underlying element in the pathogenesis of autoimmune diseases such as systemic lupus erythematosus, membranous glomerulonephritis, and others [12,13].…”
Section: Introductionmentioning
confidence: 99%